Sinophone verses from lyrical (e)scapes: an account of poetics and poïesis in distress (Altre Modernità, 2022)
The initial outburst of the pandemic, in early 2020, forced China and the rest of the world into seclusion, anxiety, social alienation. In the Sinosphere, a human response to the aporia of isolation is the lyrical production, a prosperous literary activity through which the individual gives shape to a collective consciousness.The present paper examines a collection of Sinophone verses sprung from the Covid-19 threat and dismay, as a psychic necessity to re-organize the perception of the outer world. Specifically, it studies a body of fifty-two poems composed by twelve lyrical Sinophone voices, published in Chinese in a spring number of the respected literary journal Jintian 今天. This investigation primarily focuses on the cultural, aesthetic, and psychological value of a lyrical polyphony embodied by unchained Sinophone voices, which sing against the background of a common predicament. In parallel, it reads the collection as a collective memory and a cultural repository, engendered by a narrative projection of experience: to that end, it combines a narratological approach with the observation of certain lyrical features of a “poetics of distress”.